Evidence and Potential Mechanism of Action of Lithospermum erythrorhizon and Its Active Components for Psoriasis - Wang, Jiao; Liu, Liu; Sun, Xiao-Ying; Zhang, Shuo; Zhou, Ya-Qiong; Ze, Kan; Chen, Si-Ting; Lu, Yi; Cai, Xiao-Ce; Chen, Jia-Le; Luo, Ying; Ru, Yi; et al. (Frontiers in Pharmacology, 2022)
Background: Chinese herbal medicine is effective in the treatment of psoriasis and can significantly reduce skin inflammation and psoriatic lesions, with few side effects. shikonin (SHI) and β, β-dimethylacryloyl alkannin (DMA), the main effective components of Lithospermum, have strong anti-inflammatory effects. The aim of this systematic review was to evaluate the efficacy and safety of Lithospermum and its main active components and elucidate the potential mechanisms of their action in psoriasis treatment. Methods: Seven databases were systematically searched. We included clinical and preclinical studies that examined the effects of Lithospermum and its active components on psoriasis. All data were analyzed using the RevMan 5.3 software. The Cochrane risk-of-bias tool and SYRCLE’s risk-of-bias tool were used to assess the quality of all studies. Results: 11 clinical trials and 23 preclinical studies were assessed in this study. Meta-analysis showed that, when treating psoriasis patients, the herbal decoction (Lithospermum as the monarch drug) can significantly improve psoriatic dermatitis, which can significantly reduce the psoriasis area and severity index (PASI) score (mean difference [MD]=-2.00, 95% confidence interval [CI] [-3.19, -0.80], P=0.001; I²=85%). The incidence rates of diarrhea (risk ratio =0.21, 95% [CI] [0.06, 0.81], P=0.02) were higher in the Lithospermum group than in the control group, while other adverse events were not significantly different between the two groups (p>0.05). We evaluated the PASI score of mice on day 7, and found that SHI or DMA also alleviated psoriatic lesions (MD=-3.36, 95% CI [-4.67, -2.05], P<0.00001, I²=94%). Furthermore, the epidermal thickness decreased more after SHI or DMA treatment compared to the control group (MD=-34.42, 95%CI [-41.25, -27.59], P<0.00001, I²=93%). Based on the preclinical studies, we also summarized and mapped the mechanisms of SHI and DMA in the treatment of psoriasis. Conclusion: Available findings demonstrated that Lithospermum combined